2015
DOI: 10.5846/stxb201304060609
|View full text |Cite
|
Sign up to set email alerts
|

The physiological adaptation mechanisms of four common desert species in response to desert environments

Abstract: 摘要:选择 3 个温带沙地 (松嫩沙地、 呼伦贝尔沙地、 科尔沁沙地) 4 个共有种沙生植物 (黄柳 (Salix gordejevii) 、 差巴嘎 蒿 (Artimisia halodendron) 、扁蓿豆(Melissitus ruthenica) ,猪毛菜(Salsola collina) ,通过自然状况下其叶片抗氧化酶活力和渗透调节 物及丙二醛(MDA) 含量日变化分析,探讨抗氧化酶活力和渗透调节物在沙生植物适应沙漠环境强光辐射和温度日变化中的作 用,以及不同科属沙生植物抗逆生理调控机理的差异。 结果表明:(1) 不同沙地的 4 个共有沙生植物种可通过自身快速生理代 谢调解,积累渗透调节物、提高抗氧化酶活力应对沙漠环境强光辐射和温度日变化,但生理调控幅度较小。 (2) 3 个沙地不同科 属的 4 个共有种在渗透调节物含量和抗氧化酶活力及种类上存在差异。 扁蓿豆叶片日均 MDA 含量、 POD(peroxidase) 活力、 CAT(catalase) 活力、脯氨酸含量均最高,分别较其它 3 个种平均高 2、10、2 和 2. 5 倍。 黄柳叶片日均 MDA 含量较高, SOD (superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Zhou R. L. explored the role of antioxidant enzyme activity and osmotic regulatory substances in the adaptation of sandy plants to desert environments in three temperate sandy lands, as well as their physiological regulatory mechanisms. The results showed that although different types of sandy plants have different physiological regulatory mechanisms for desert environment adaptation, different plants can adapt to different environmental conditions by regulating their own physiological, biochemical, and metabolic processes [37], which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Zhou R. L. explored the role of antioxidant enzyme activity and osmotic regulatory substances in the adaptation of sandy plants to desert environments in three temperate sandy lands, as well as their physiological regulatory mechanisms. The results showed that although different types of sandy plants have different physiological regulatory mechanisms for desert environment adaptation, different plants can adapt to different environmental conditions by regulating their own physiological, biochemical, and metabolic processes [37], which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%